2010
DOI: 10.1306/intro060110
|View full text |Cite
|
Sign up to set email alerts
|

Sandstone reservoir quality prediction: The state of the art

Abstract: Subsequently, she has worked a variety of Exploration Company assignments in the North Sea, Gulf of Mexico, and Middle East. Her current interests are in predicting the distribution of early diagenetic controls on deep reservoir quality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
116
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 225 publications
(118 citation statements)
references
References 54 publications
2
116
0
Order By: Relevance
“…There are many studies where deep reservoir porosity is linked to early diagenetic clay or microquartz grain coats (e.g. Pittman et al, 1992;Ehrenberg, 1993;Aase et al, 1996;Bloch et al, 2002;Ajdukiewicz and Lander, 2010;Ajdukiewicz and Larese, 2012;French et al, 2012;Worden et al, 2012). These studies have shown that quartz-rich sandstones with well-developed and continuous diagenetic clay or microquartz grain coats contain a much lower volume of macro-quartz cement than without such coatings (Ajdukiewicz and Lander, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…There are many studies where deep reservoir porosity is linked to early diagenetic clay or microquartz grain coats (e.g. Pittman et al, 1992;Ehrenberg, 1993;Aase et al, 1996;Bloch et al, 2002;Ajdukiewicz and Lander, 2010;Ajdukiewicz and Larese, 2012;French et al, 2012;Worden et al, 2012). These studies have shown that quartz-rich sandstones with well-developed and continuous diagenetic clay or microquartz grain coats contain a much lower volume of macro-quartz cement than without such coatings (Ajdukiewicz and Lander, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…8l). The importance of grain coating chlorite in preserving porosity has been recognized in many studies (Bloch et al, 2002;Ehrenberg et al, 2009;Ajdukiewicz and Lander, 2010;Tobin et al, 2010;Taylor et al, 2010;Ozkan et al, 2011;Deschamps et al, 2012;Nguyen et al, 2013). For Chang 8 sandstone, where chlorite rims are present, the formation of quartz overgrowths is actually inhibited and thus porosity being preserved (Fig.…”
Section: Chloritementioning
confidence: 92%
“…Diagenetic heterogeneities strongly influence reservoir performance and fluid flow (Deschamps et al, 2012). Effective resource exploitation requires comprehensive reservoir description and characterization to identify the reservoir properties in such diagenetically heterogeneous sandstones (Ozkan et al, 2011), it is of great significance to consider the impact of diagenetic processes and diagenetic minerals on reservoir quality, and this could provide a powerful tool to predict the high quality reservoirs within sandstone successions (Higgs et al, 2007;Ajdukiewicz and Lander., 2010;Morad et al, 2010;Tobin et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Chlorite has been widely reported as an important grain coating clay mineral inhibiting quartz overgrowth and help preserve porosity (Bloch et al, 2002;Ehrenberg, 1993;Stricker and Jones, 2016;Taylor et al, 2010). Bloch et al (2002) and Ajdukiewicz and Lander (2010) (Stricker et al, 2016a). Hence overpressure and importantly low vertical effective stress has less impact upon porosity maintenance in the Norwegian sector, which explains the poorer reservoir quality and higher degree of compaction.…”
Section: Comparison With Skagerrak Formation In Uk Sectormentioning
confidence: 99%